Pemberlakuan Sanksi Terhadap Pelaku Penjual Obat Terapi Covid-19 diatas Harga Eceran Tertinggi (HET) - Putu Pebri Theresia Ananda; I Nyoman Gede Sugiartha; Diah Gayatri Sudibya (Fakultas Hukum Universitas Warmadewa, 2022)
The spread Covid-19 in Indonesia has circulated a lot about how to recover quickly if affected by the Covid-19 therapeutic drugs Covid-19, because many people who buy these drugs have made sellers selling above HRP appear which are detrimental to consumers. HRP has been regulated in Indonesia so that no rogue sellers sell goods above a predetermined price so that they do not harm consumers and are subject to sanctions if there are perpetrators who sell Covid-19 above HRP. This thesis discusses the regulation of drug HRP based on the decision of the Minister of Health and the imposition of sanctions on perpetrators of selling Covid-19 above HRP. This research uses normative legal research with a statutory approach. The results of this study indicate that the regulation of drug HRP is based on the Decree of the Minister of Health concerning the price of drug and the imposition of sanctions on perpetrators of selling Covid-19 above HRP in accordance with the provisions Article 62 paragraph (1) UUPK, Law no. 36 of 2009 concerning Health, and Article 7 paragraph (1) of the Minister of Trade Regulation no. 57 of 2017.